Optimal Pin Fin Arrangement of Heat Sink Design and Thermal Analysis for Central Processing Unit - Mohd Annuar, Khalil Azha; Ismail, Fatimah Sham (2014)
Heat sink is the most popular device used for electronic cooling. A continuing in increasing of power density in CPU processor, by reducing the size of electronic products has led to the importance of thermal management issue in this industry. This issue will reduce the performance of the CPU processor and indirectly affects the lifetime of the electronics package. In order to avoid these consequences, therefore, heat sink with high heat transfer rate is need. The selection of suitable heat sink geometries requires a compromise among the availability of space, weight, and cost as well as the heat transfer characteristics of the heat sink model surface. This study aims to provide the optimal arrangement of heat sink by using random approach that randomly generated the position of pin by visualized the thermal profile using COMSOL Multiphysics software. The finding of this study propose a new arrangement (optimal) of the pin fin that be able to give better thermal performance which are 2.84 percent and 0.63 percent compared to the conventional design, which is inline and staggered arrangement. To develop a simple and effective random approach arrangement can significantly contribute to the advancement of thermal performance solution and catering the industrial needs.